Reduction of Current Collapse in GaN High-Electron Mobility Transistors Using a Repeated Ozone Oxidation and Wet Surface Treatment - Lin, Shuxun; Wang, Maojun; Xie, Bing; Wen, Cheng P.; Min Yu; Wang, Jinyan; Hao, Yilong; Wu, Wengang; Huang, Sen; Chen, Kevin J.; Shen, Bo (IEEE ELECTRON DEVICE LETTERS, 2015)
This letter reports a GaN high-electron mobility transistor (HEMT) with reduced current collapse using a multicycle combined plasma-free ozone oxidation and wet surface treatment before Si3N4 passivation. The surface oxide and decomposed layers could be effectively removed and a perfect AlGaN surface is obtained after the treatment. Pulsed IV and RF power measurement indicate that the current collapse is greatly suppressed due to the removal of imperfect surface layer and damage free nature, providing an effective surface treatment method to improve the effect of passivation in GaN HEMT.